Dinamika Kelompok Tani dan Keberhasilan Program Asuransi Usahatani Padi di Pekon Tulung Agung Kecamatan Gadingrejo Kabupaten Pringsewu - Avelia, Fitra; Hasanuddin, Tubagus; Prayitno, Rio Tedi (Suluh Pembangunan : Journal of Extension and Development, 2021)
This research aims to find out the level of dynamics of the farmer group, the success rate of the Rice Farm Insurance (AUTP) program, factors related to the success of the Rice Farm Insurance (AUTP) program, and the relationship between the dynamics of the farmer group and the success of the Rice Farm Insurance (AUTP) program in Pekon Tulung Agung, Gadingrejo Subdistrict, Pringsewu Regency. This research was conducted in Pekon Tulung Agung, Gadingrejo Subdistrict, Pringsewu Regency. Data collection on this study was conducted in June 2021. Respondents to this study were 76 farmers who belonged to the farmer group. The study used surveying and data testing methods using non-parametric statistics of Spearman Rank correlation tests. The results showed that the level of dynamics of the farmer group was in a fairly dynamic category, the success rate of the Rice Farm Insurance (AUTP) program was in the less successful category, the factor associated with the success of the Rice Farm Insurance (AUTP) program was the age of farmers, and there was a real relationship between the dynamics of the farmer's group and the success of the Rice Farm Insurance (AUTP) program.